PARTISIPASI POLITIK PEMILIH PEMULA PADA PILKADA KOTA PARIAMAN TAHUN 2018 - Rahmad Fadli; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Participation is a form of role and participation itself in the activity of planning and implementation to achieve the purpose of developing the society. The manifestation of community participation can be in the form of service, suggestion, or material either directly or indirectly. Likewise the beginner voters that can assist and participate in the implementation of Regional Head Election in 2018. This research was conducted in Pariaman City, West Sumatera Province. The purposes of this research were to know the participation manifestation of beginner voters in the implementation of Regional Head Election in Pariaman City in 2018 and to know the factors that affect beginner voters. Besides, this research also aimed to know how was the participation level of those beginner voters. This research used descriptive-qualitative method. In this research, the researcher used data collection technique such as Simple Random Sampling method. Data needs covered primary data obtained through filling the questionnaires and secondary data with total population were 717 respondents. In this research, the writer used slovin formula to obtain the number of samples in which the writer took precision level in the amount of 10% from total population. The research results show that the participation manifestation of beginner voters at Regional Head Election in Pariaman City in 2018 is in the form of being active to do the vote. At the category of participation manifestation, the beginner voters are at rank 7 in which it is at low category of participation level, and the percentage is 54,6%. While the factors that affect beginner voters to be active in joining the election activity is their knowledge about politics and the implementation of regional head election. The effect of respondents’ knowledge is 43%.